2022
DOI: 10.3390/s22062243
|View full text |Cite
|
Sign up to set email alerts
|

Reported Outcome Measures in Studies of Real-World Ambulation in People with a Lower Limb Amputation: A Scoping Review

Abstract: Background: The rapidly increasing use of wearable technology to monitor free-living ambulatory behavior demands to address to what extent the chosen outcome measures are representative for real-world situations. This scoping review aims to provide an overview of the purpose of use of wearable activity monitors in people with a Lower Limb Amputation (LLA) in the real world, to identify the reported outcome measures, and to evaluate to what extent the reported outcome measures capture essential information from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 126 publications
(629 reference statements)
0
7
0
Order By: Relevance
“…Improvements in activity monitoring technology are advancing the characterization of prosthesis use in people with lower-limb amputation, allowing researchers to extend beyond the traditional measurements of step count and cadence to more fully characterize prosthesis users' clinical outcomes. 2 Activities such as working at a counter or moving items around while sitting at a desk may soon be detectable, for example. Providing body support to enable these actions is a key function of the prosthesis from the user’s perspective, but one that is rarely measured using traditional step counting technologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements in activity monitoring technology are advancing the characterization of prosthesis use in people with lower-limb amputation, allowing researchers to extend beyond the traditional measurements of step count and cadence to more fully characterize prosthesis users' clinical outcomes. 2 Activities such as working at a counter or moving items around while sitting at a desk may soon be detectable, for example. Providing body support to enable these actions is a key function of the prosthesis from the user’s perspective, but one that is rarely measured using traditional step counting technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have pursued this type of investigation, most of them delineating sitting, standing, lying, and stepping. 2 Others extended from these types of activities to delineate the time-of-day steps were taken, 16 durations of activities, 17 or the direction of movement. 3,9 In the present study, we sought to extend from those efforts by developing a sensor capable of measuring weight shifts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mellema and Gjøvaag [1] conducted a scoping review to evaluate the purpose and reported outcome measures of wearable activity monitors in people with a lower limb amputation (LLA) in real-world situations. The review found that step count was the most frequently reported outcome measure, but caution is needed in choosing reliable outcome measures.…”
Section: Contributionsmentioning
confidence: 99%
“…However, since walking is an essential part of daily life, those with an LEA suffer from significant loss of mobility, which is inconvenient and causes hardship [4,6]. Prosthesis use can disguise the partial or complete loss of a lower limb in appearance, while assisting those with an LEA to walk or participate in daily activities and enjoy a certain amount of physical movement and ability to self-care [7][8][9]. In recent years, there has been growing research interest on prosthetic feet.…”
Section: Introductionmentioning
confidence: 99%